2015
DOI: 10.1249/mss.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrostimulation with Blood Flow Restriction on Muscle Size and Strength

Abstract: Low-intensity NMES-BFR induces muscle hypertrophy and strength gain in untrained young male participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 27 publications
2
47
1
1
Order By: Relevance
“…More recently the combination of NMES with BFR has been investigated. The results of trials using NMES and BFR in humans are varied, with two studies reporting increased muscle strength and hypertrophy compared with NMES and BFR alone in healthy and spinal cord injured adults 11,12 one showing increased strength follloiwng NMES with BFR compared to a control group 13 and on demonstrating no added benefit 14 . Although mixed results have currently been observed, the clinical application for NMES and BFR increasing muscle strength and size post-surgery or during immobilisation when voluntary exercise is contraindicated, is promising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently the combination of NMES with BFR has been investigated. The results of trials using NMES and BFR in humans are varied, with two studies reporting increased muscle strength and hypertrophy compared with NMES and BFR alone in healthy and spinal cord injured adults 11,12 one showing increased strength follloiwng NMES with BFR compared to a control group 13 and on demonstrating no added benefit 14 . Although mixed results have currently been observed, the clinical application for NMES and BFR increasing muscle strength and size post-surgery or during immobilisation when voluntary exercise is contraindicated, is promising.…”
Section: Introductionmentioning
confidence: 99%
“…Varied methodologies have led to conflicting findings in studies investigating NMES and BFR, thus limiting the understanding of underlying physiological mechanisms that induce changes in muscle strength and hypertrophy. The NMES protocols currently utilised have considerable variability, with frequencies ranging from 20-100 Hz and unclear reporting of other parameters including stimulation intensities [11][12][13][14] . To maximise quadriceps strength after NMES it is recommended to use a frequency of 50 Hz, maximal tolerable intensities and to place stimulating electrodes over muscle motor points 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of additive or synergistic interaction(s) between the mechanical and ischemic stimuli in BFRRE has been hypothesized previously and might in part explain how loads as low as 20% of 1RM can result in marked muscle hypertrophy, despite seemingly producing only moderate mechanical stress even in the “functional ablation” scenario outlined above. Although still somewhat speculative, there are good reasons to postulate such interactions, given that heat stress alone and repeated brief ischemia‐reperfusion alone have been shown to induce muscle hypertrophy in some studies and that concomitant blood flow restriction can potentiate the muscle hypertrophy and strength gains resulting from electrically stimulated contractions. Furthermore, Goto et al reported that unilateral low‐intensity resistance exercise for the elbow flexors combined with heat stress in the same arm resulted in increased elbow flexor muscle CSA, whereas the same unilateral exercise protocol alone did not produce any hypertrophy in the contralateral arm.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a novel concept, studies combining low-intensity NMES with BFR have found increases in muscle size and strength. (98,99) NMES of the quadriceps does not involve transmission of large forces through the tibiofemoral joint, thus exhibiting a low risk of damaging the graft or exacerbating any cartilage, meniscal or bone injuries. Early increases in muscle strength and size are necessary to perform voluntary training later in the rehabilitation process, (100) and there is debate over whether passive BFR alone is truly effective.…”
Section: Bfr In Acl Rehabilitation: a Progressive Model Phase 1: Earlmentioning
confidence: 99%